Zaveshchanie Very Mukhinoi . Zaveshchanie Very Mukhinoi . Vera Muhina's Will . Завещание Веры Мухиной - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by the state television (Moscow) in the USSR and recorded by the Radio Liberty Monitoring Unit in Munich as part of their effort to track and analyze the official media of the republics of the Soviet Union. Передача государственного телевидения (Москва, СССР) была записана отделом мониторинга радиостанции Свобода (Мюнхен) как часть проекта по анализу официальных средств информации республик Советского Союза. The documentary explores the life and work of sculptor Vera Muchina. Featured in the program: Mukhina, Vera Ignat'evna (Sculptor); Shadr, Ivan Dmitrievich (Sculptor) Contributors: Derbysheva, L. (Director); Akabalieva, G. (Editor); Maev, V. (Camera); TSentral'naia Studiia Dokumental'nykh Fil'mov (Studio) О жизни и творческой судьбе скульптора В. Мухиной. В программе участвуют: Мухина, Вера Игнатьевна (Скульптор); Шадр, Иван Дмитриевич (Скульптор) Создатели: Дербышева, Л. (Режиссер); Акабалиева, Г. (Редактор); Маев, В. (Оператор); Центральная Студия Документальных Фильмов (Студия)